How actors are (dis)integrating policy agendas for multi-functional blue and green infrastructure projects on the ground. Issue 1 (2nd January 2021) - Willems, Jannes J.; Kenyon, Anna V.; Sharp, Liz; Molenveld, Astrid
ABSTRACT: Local governments are increasingly considering blue and green infrastructure (BGI) in order to climate-proof cities. Because BGI can have multiple benefits beyond climate adaptation, policy integration is required. Since drainage services have traditionally been within the remit of a single department, this is new territory for water management. This article provides a dynamic perspective on the messy process of policy integration 'on the ground' in two BGI projects in Dordrecht, NL and Bradford, UK. Drawing on interviews with key actors involved in the cases, our research question is: How are ambitions to integrate policies resulting in multi-functional BGI projects? While previous research typically defines organisational structures as barriers for policy integration, our findings demonstrate instances of actors who are successfully navigating these structures as a route towards policy integration. Nevertheless, we found that actors who push for BGI lack resources and authority, so they mainly rely on more voluntary forms of policy integration that involve concerted action over a number of years. Overall, our cases demonstrate that space for policy integration exists and powerful agencies are sympathetic to this, but more support is needed to achieve this mandate.